Early‐phase clinical trial eligibility and response evaluation criteria for refractory, relapsed, or progressive neuroblastoma: A consensus statement from the National Cancer Institute Clinical Trials Planning Meeting. Issue 21 (13th September 2022) - Park, Julie R.; Villablanca, Judith G.; Hero, Barbara; Kushner, Brian H.; Wheatley, Keith; Beiske, Klaus H.; Ladenstein, Ruth L.; Baruchel, Sylvain; Macy, Margaret E.; Moreno, Lucas; Seibel, Nita L.; Pearson, Andrew D.; et al.
Abstract : Background: International standardized criteria for eligibility, evaluable disease sites, and disease response assessment in patients with refractory, progressive, or relapsed high‐risk neuroblastoma enrolled in early‐phase clinical trials are lacking. Methods: A National Cancer Institute–sponsored Clinical Trials Planning Meeting was convened to develop an international consensus to refine the tumor site eligibility criteria and evaluation of disease response for early‐phase clinical trials in children with high‐risk neuroblastoma. Results: Standardized data collection of patient and disease characteristics (including specified genomic data), eligibility criteria, a definition of evaluable disease, and response evaluations for primary and metastatic sites of disease were developed. Eligibility included two distinct patient groups: progressive disease and refractory disease. The refractory disease group was subdivided into responding persistent disease and stable persistent disease to better capture the clinical heterogeneity of refractory neuroblastoma. Requirements for defining disease evaluable for a response assessment were provided; they included requirements for biopsy to confirm viable neuroblastoma and/or ganglioneuroblastoma in those patients with soft tissue or bone disease not avid for iodine‐123 meta‐iodobenzylguanidine. Standardized evaluations for response components and time intervals for response evaluations were established. Conclusions: The use of international consensus eligibility, evaluability, and response criteria for early‐phase clinical studies will facilitate the collection of comparable data across international trials and promote more rapid identification of effective treatment regimens for high‐risk neuroblastoma. Abstract : This international consensus statement from a National Cancer Institute‐sponsored Clinical Trials Planning Meeting refines the tumor site eligibility criteria and evaluation of disease response for early‐phase clinical trials in children with high‐risk neuroblastoma.